Development of Students’ Counseling System in the Division of Students Affairs in State University - Panatungtirawit, Anongpanuch .; Namwan, Tharinthorn (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this research were: 1) to study the component of students’ counseling system for the division of student affairs in State University, 2) to study the current situation, desirable situation, and need, 3) to            try                        out                     the                      counseling         system,                        and4) to evaluate the Propriety, Feasibility, and Utility. The samples were 435 heads of working group, counseling practitioners, and counselors in State University. The research instruments were: 1) the Interview Form, 2) the Questionnaire, and 3) the Evaluative Form. The statistic using for data analysis consisted of the Percentage, Mean, Standard Deviation, and Modified Priority Needs Index technique. The research findings found that: 1) there were 3 systems of students’ counseling system including: (1) the Educational Counseling, (2) the Occupational Counseling, and (3) the Personal and Social Counseling. In addition, there were 4 major components including: (1) the Input, (2) the Process, (3) the Output, and (4) the Feedback. 2) The current situation and desirable situation, in overall, was in “High” level. The needs were ranked in order from high to low as follows: (1) the Personal and Social Counseling, (2) the Educational Counseling, and (3) the Occupational Counseling. 3) The findings in trying out the developed counseling system, were in “the Highest” level. 4) The evaluative findings in Propriety, Feasibility, and Utility of counseling system, found that: (1) the findings of measuring in knowledge and comprehension in counseling were increased, and (2) the overall competency, in overall, was in “High” level.